Analysis of Customer Satisfaction Survey Results at the Large Ship Mooring at PT Pelabuhan Indonesia Regional 2 Cirebon Branch - Dimas Widi Dwiputra; Prafieta Amarta; Teddy Arif Permana; Siti Khumayah; Aghnia Diah Lestari (Journal of World Science, 2024)
Survey results in customer satisfaction are essential for a company because, with a survey, the company can know the needs of its customers, help improve employee performance, make the right decisions, and encourage company growth. PT Pelabuhan Indonesia (Persero) Regional 2 Cirebon Branch, one of the Port Business Entities (BUP), conducts activity surveys. The research is studied about the satisfaction of customers at PT Pelabuhan Indonesia (Persero) Regional 2 Cirebon Branch. This research gathers information through documentation, interviews, direct observations, and a study library. The study results are Dimensions of Direct Evidence, such as appearance officers and comfort facilities. Dimensions Reliability includes an attitude of polite courtesy, justice in getting services, and transparent service standards. Responsiveness Dimensions include being a? responsiveness officer in handling requests and complaints from Customers. Dimension guarantees include speed, accuracy, and time service. Dimension Empathy is an officer's ability to notice customers' desires and needs.